Participation in Courts and Tribunals : Concepts, Realities and Aspirations - Jacobson, Jessica (Book collections on Project MUSE., 2020)
This significant study reveals how participation is supported in the courts and tribunals of England and Wales. Including reflections on changes to the justice system as a result of the COVID-19 pandemic, it details the socio-structural, environmental, procedural, cultural and personal factors which constrain it.